Sustainability Accounting: Environmental, Social and Governance (ESG) Disclosures, Low Carbon Economy and Green Initiatives. - Uswatul Fajar Nurfatimah; Yusron Difinubun; Annisa' Khaerani (Program Studi Akuntansi Unimuda Sorong, 2024)
This study aims to determine the disclosure of Environmental, Social, And Governance (ESG) on Low Carbon Economy which is moderated by Green Initiatives. This research is a descriptive quantitative research type. The sample of this research is 51 companies listed on the Indonesia Stock Exchange that have participated in PROPER (Company Performance Rating Assessment Programme in Environmental Management) for the 2019-2022 period. This study uses judgement sampling technique and PLS (Partial Least Square) analysis method, the data is processed using SmartPLS 4.0 software. The results found that Environmental, Social and Governance (ESG) disclosure has a negative effect on Low Carbon Economy (LCE). In addition, Environmental, Social, and Governance Disclosure has a positive and significant effect on Low Carbon Economy which is moderated by Green Initiatives. The novelty of this research is that it uses Environmental, Social and Governance (ESG) disclosure variables on Low Carbon Economy and Green Initiatives. The results of testing the moderation determination of this study are Low Carbon Economy (LCE) of 42%.